Identifikasi Kesulitan Pelaksanaan Pembelajaran Dalam Jaringan (Daring) Di Masa Pandemi Covid-19 Pada Mahasiswa Program Studi Pendidikan Kimia FKIP Universitas Mataram - Istiana, Dina; Siahaan, Jeckson; Junaidi, Eka; Hakim, Aliefman (FKIP University of Mataram, 2024)
This study aims to describe the difficulties of implementation online learning during the covid-19 pandemic to students of Chemistry Education Program at Mataram of University. This type of research is descriptive research with a qualitative approach. The population of this study is 229 students of the Chemistry Education Program at Mataram of University in semester II, IV and VI. The samples were questionnaires and interviews. The result showed that; 1) Learning difficulties in subject considered difficult by students of the Chemistry Education Program at the University of Mataram in the implementation of online learning during the covid-19 pandemic were organic chemistry courses with a percentage of 45%; 2) The highest difficulties faced by students in the implementation of online learning during the covid-19 pandemic were caused by aspect of the student’s socioeconomic conditions with a percentage of 84% in the very high category; 3) The lowest the covid-19 pandemic were organic chemistry courses with a percentage of 45%; 2) The highest difficulties faced by students in the implementation of online learning during the covid-19 pandemic were caused by aspect of the student’s social economic interaction with a percentage of 64% in the high category.